Effectiveness of patients’ knowledge about perioperative information prior to third molar removal - Kolte, Vrinda; Shenoi, Ramakrishna; Ghodeswar, Shefali; Garg, Anoop; Bang, Kshitij (International Journal of Dental Research, 2014)
Many patients feel anxious before dental treatment on the presumption that the procedure will cause them pain and discomfort. Among other procedures, oral surgery has been reported to induce highest level of anxiety. The surgical removal of mandibular third molars is one of the most commonly performed dent alveolar procedures in oral and maxillofacial surgery. Individuals of lower socioeconomic status, with less education and lack of knowledge about the procedure are one major factor to preoperative anxiety. Provide preoperative information about the procedure significantly reduces patient anxiety. Several preoperative variables were recorded (during preoperative, intraoperative and postoperative phases) and patient anxiety was assessed through the use of various questionnaires.